2021
DOI: 10.1186/s40104-020-00524-4
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptomic analysis reveals Lnc-ADAMTS9 exerting an essential role in myogenesis through modulating the ERK signaling pathway

Abstract: Background Long non-coding RNAs (lncRNAs) are emerging key regulators involved in a variety of biological processes such as cell differentiation and development. The balance between myogenesis and adipogenesis is crucial for skeletal muscle homeostasis in humans and meat quality in farm animals. The present study aimed to reveal the global transcriptomic profiles of adipogenic (Adi-) and myogenic (Myo-) precursors derived from porcine skeletal muscle and identify lncRNAs involved in the modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Together, these factors cooperatively regulate the controlled process of myoblast proliferation and differentiation. Recent studies further revealed that various non-coding RNA species, including lncRNA [ 7 , 8 , 9 ], miRNA [ 10 , 11 , 12 ], and circRNA [ 13 , 14 , 15 ], participate in the regulation of myogenesis. In particular, circular non-coding RNA molecules (circRNAs) are increasingly recognized as key regulatory factors of various biological processes, but their functional roles in myogenesis remain poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Together, these factors cooperatively regulate the controlled process of myoblast proliferation and differentiation. Recent studies further revealed that various non-coding RNA species, including lncRNA [ 7 , 8 , 9 ], miRNA [ 10 , 11 , 12 ], and circRNA [ 13 , 14 , 15 ], participate in the regulation of myogenesis. In particular, circular non-coding RNA molecules (circRNAs) are increasingly recognized as key regulatory factors of various biological processes, but their functional roles in myogenesis remain poorly defined.…”
Section: Introductionmentioning
confidence: 99%